2015
DOI: 10.1210/jc.2015-2330
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin Ligands and Receptors Are Expressed in the Human Fetal Ovary and Regulate Germ Cell Expression ofCOX2

Abstract: Developmental changes in expression and regulation of COX2 and phosphorylated ERK (pERK) by PROK1 suggest that PROK ligands may be novel regulators of germ cell development in the human fetal ovary, interacting within a network of growth and survival factors prior to primordial follicle formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The number of germ cells in fetal ovaries peaks around 20-22 GW with 5-7 × A c c e p t e d M a n u s c r i p t 5 10 6 cells but during the last part of fetal development the number is reduced to around 7 × 10 5 oocytes that are present at birth [50]. Oogonial proliferation, meiotic entry and the formation of primordial follicles (oocytes) depend on the interaction with somatic cells, primarily granulosa cells, and the somatic 'cell streams' surrounding the germ cell clusters [51][52]. An essential factor for granulosa cell differentiation is FOXL2, which is detectable already from 8 GW [27,51].…”
Section: Fetal Ovarymentioning
confidence: 99%
“…The number of germ cells in fetal ovaries peaks around 20-22 GW with 5-7 × A c c e p t e d M a n u s c r i p t 5 10 6 cells but during the last part of fetal development the number is reduced to around 7 × 10 5 oocytes that are present at birth [50]. Oogonial proliferation, meiotic entry and the formation of primordial follicles (oocytes) depend on the interaction with somatic cells, primarily granulosa cells, and the somatic 'cell streams' surrounding the germ cell clusters [51][52]. An essential factor for granulosa cell differentiation is FOXL2, which is detectable already from 8 GW [27,51].…”
Section: Fetal Ovarymentioning
confidence: 99%
“…In an experimentation conducted by Sharon et al , the expression of COX-2 protein was significantly increased after the treatment of PROK1 in a human germ cell tumor line. And it was confirmed that PROK1 signaling via PROKR1 induce the expression of COX-2 protein 23 . Another research showed that PROK1 induced COX-2 expression and prostaglandin synthesis in human endometrial cells and first trimester decidua via a Gq coupled pathway 56 .…”
Section: Role Of Prokineticin1 In Normal Pregnancymentioning
confidence: 77%
“…Successful embryo implantation may be predicted by PROK1 concentration in the follicular fluid and fertilization culture media in conventional in vitro fertilization-embryo transfer 22 . Moreover, expression of PROK1 and PROK2 is correlative to the germ cell development in the human fetal ovary 23 . PROK1 increases ERK phosphorylation and COX2 expression 23 .…”
Section: Biological Functions Of the Prokineticin1mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these data are related to human reproduction. Eddie et al described the action of EG-VEGF being highest in the midgestation (17–21 weeks) ovaries by the increase of ERK phosphorylation and elevated COX-2 expression [37]. It seems that EG-VEGF levels in normal ovaries influence the endometrium receptivity during implantation.…”
Section: The Mechanism Of Action Of Eg-vegf Moleculementioning
confidence: 99%